Genetic Improvement of U.S. Soybean in Maturity Groups II, III, and IV. Issue 4 (1st July 2014) - Rincker, Keith; Nelson, Randall; Specht, James; Sleper, David; Cary, Troy; Cianzio, Silvia R.; Casteel, Shaun; Conley, Shawn; Chen, Pengyin; Davis, Vince; Fox, Carolyn; Graef, George; et al.
ABSTRACT: Soybean improvement via plant breeding has been critical for the success of the crop. The objective of this study was to quantify genetic change in yield and other traits that occurred during the past 80 yr of North American soybean breeding in Maturity Groups (MGs) II, III, and IV. Historic sets of 60 MG II, 59 MG III, and 49 MG IV soybean cultivars, released from 1923 to 2008, were evaluated in field trials conducted in 17 U.S. states and one Canadian province during 2010 to 2011. Averaged over 27 MG II and MG IV and 26 MG III site‐years of data, the estimated rates of yield improvement during the 80 yr were 23 kg ha –1 yr –1 for MGs II and III, and 20 kg ha –1 yr –1 for MG IV cultivars. However, a two‐segment linear regression model provided a better fit to the data and indicated that the average current rate of genetic yield gain across MGs is 29 kg ha –1 yr –1 . Modern cultivars yielded more than old cultivars in all environments, but particularly in high‐yielding environments. New cultivars in the historic sets used in this study are shorter in height, mature later, lodge less, and have seeds with less protein and greater oil concentration. Given that on‐farm soybean yields in the United States are also increasing at a rate of 29 kg ha –1 yr –1, it can be inferred that continual release of greater‐yielding cultivars has been a substantive driver of the U.S. on‐farm realized yield increases.